Optimum Individual Income Tax (Economic and Political Thought, 2010)
The aim of the present work is to present selected views of specialists infinancial law and economics on the desired shape taxation system, especiallycorporate income tax. The author tries to do this in a clear way for lawyersand economists as well as laypersons.Firstly, the article discusses some demands for the taxation system madeby economists and presents short-term effects of taxation policy based on theIS-LM model. Next, it presents selected opinions of the financial law doctrineon income tax, especially corporate income tax. The article also containsa description of selected institutions of American tax law and some proposalsto make use of American experiences in Poland.The article is an attempt to take a wide approach to the issue of incometax, especially corporate income tax, including economic opinions as wellas fiscal and legal views. Such a broad approach to the issue is a result ofa conviction that issues connected with taxation lie on the meeting groundfor interests of two sciences which seem to be very distant from each other:law and economics.